“GURU SUSRUSA”; NILAI PENDIDIKAN KARAKTER PADA TEKS ADI PARWA BAGIAN CERITA BHAGAWAN DOMYA - Putu Widhi Kurniawan; Made Reland Udayana Tangkas (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2023)
The text of Adi Parwa as the first part of the 18 parwa (Asta Dasa Parwa) is one of the parwa literature that is in great demand among observers of Old Javanese literature. How could it not be, the parwa contains various stories behind the occurrence of the Mahabhatara story (the Indian version of the term) which eventually led to a big war written on kakawin Bharathayudha. One part of Adi Parwa's story that is quite well known and is very thick with educational values is the story of Bhagawan Domya who has three students namely Sang Arunika, Sang Utamanyu, and Sang Weda. Each was given a very difficult task to test his loyalty and sincerity in studying Vedic science. There is one important note in the test which is oriented towards how a student is obliged to his teacher who is called "guru susrusa". The task given by Bhagawan Domya describes an initiative to strengthen a student's mental and spiritual pursuit of knowledge. To prove this, the loyalty of the three of them is tested in sacrifice, understanding the rights and obligations of a student, and the value of a teacher's gift. Today, this aspect is important to strengthen the position of teachers and students in shaping the quality of education and the outcomes of education itself.Keywords: Adi Parwa; Master Susrusa; Character building